Understanding the Water Absorption Dynamics in Relation to Hardseededness in Mung bean (Vigna radiata L.) Genotypes - DEBASHIS PAUL; S K CHAKRABARTY; NIDHI; SUMAN DUTTA (Seed Research, 2026)
Hardseededness, common in majority of pulse crops, is considered an undesirable character whichadversely affects their culinary use. Hardseededness results from reduced permeability of the seed coat to water,hence also impacts germination. Addressing a knowledge gap in this area, the current investigation was undertakenon three hardseeded and three non-hardseeded mung bean genotypes in an attempt to understand the impact ofgenotype, storage period, and scarification treatments on water absorption dynamics in mung bean. The wateruptake patterns of three hardseeded and three non-hardseeded genotypes produced during the Kharif and summerseasons of 2019, were studied in fresh and 18-month stored control and scarified seeds. The degree ofhardseededness, judged by imbibition time, was higher in seeds produced during the Kharif season compared tothe summer season in all genotypes. Notably, non-hard seeds displayed a higher increase in weight per unit time,affirming a more rapid water uptake compared to hard seeds produced during the Kharif season. Conversely,genotypes grown in the summer season showed a lower lag phase and early radical protrusion. Stored seedsexhibited a pattern similar to those produced in the summer season with a lower lag phase duration. Scarifiedseeds demonstrated the shortest lag phase, with the second rise in water absorption occurring within 8-10 hours.It was concluded that mung bean may be cultivated in summer season for the for the purpose of seed production,and the study emphasized the effectiveness of scarification as a proven method to alleviate coat-imposed dormancy,facilitating easier water entry into the seeds and promoting early radical protrusion.